2017
DOI: 10.5607/en.2017.26.6.380
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Agmatine Induced by Ischemic Preconditioning Regulates Ischemic Tolerance Following Cerebral Ischemia

Abstract: Ischemic preconditioning (IP) is one of the most important endogenous mechanisms that protect the cells against ischemia-reperfusion (I/R) injury. However, the exact molecular mechanisms remain unclear. In this study, we showed that changes in the level of agmatine were correlated with ischemic tolerance. Changes in brain edema, infarct volume, level of agmatine, and expression of arginine decarboxylase (ADC) and nitric oxide synthases (NOS; inducible NOS [iNOS] and neural NOS [nNOS]) were analyzed during I/R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
7
0
3
Order By: Relevance
“…In this study, we confirmed that the exogenously transfected by retrovirus delivery vehicle containing human ADC gene is efficiently introduced stable, heritable genetic material into the host genome of neural stem cells and mesenchymal stem cells [1420]. We also confirmed that the endogenous ADC expression is increased in the wild-type cells and normal brain tissue in the previous study [14204445] and the present study. Nevertheless, in the further increase of ADC expression after ischemic injury, it is difficult to differentiate between the effect of ADC gene delivery and the endogenous increase in response to stress.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we confirmed that the exogenously transfected by retrovirus delivery vehicle containing human ADC gene is efficiently introduced stable, heritable genetic material into the host genome of neural stem cells and mesenchymal stem cells [1420]. We also confirmed that the endogenous ADC expression is increased in the wild-type cells and normal brain tissue in the previous study [14204445] and the present study. Nevertheless, in the further increase of ADC expression after ischemic injury, it is difficult to differentiate between the effect of ADC gene delivery and the endogenous increase in response to stress.…”
Section: Discussionsupporting
confidence: 88%
“…There is evidence to suggest that agmatine can be characterized as an inhibitory subunit for monoamide oxidase, an important neurotransmitter regulator, when administered in high concentrations (167M) [ 29 ]. NOS has been shown to be competitively inhibited by agmatine in vitro , which has a substantial impact on the function and actions of agmatine in the mammalian brain [ 17 , 30 - 32 ].…”
Section: Agmatine: Overview and Biological Significance In The Central Nervous Systemmentioning
confidence: 99%
“…Both endogenous and exogenous agmatine can exert their functions on NO and reduce ischemic brain injury in neonatal rats, levels of both are also increased during ischemic insults [ 33 , 34 ]. Kim et al [ 32 ] demonstrated the neuroprotective functions of agmatine, both in vivo and in vitro through reducing the production of NO by competitively inhibiting neuronal NOS (nNOS) and isoform NOS (iNOS). ADC is localized in astrocytes, so endogenous agmatine production is thought to be predominantly in astrocytes which are mainly absent in in vivo studies involving cultured neurons.…”
Section: Agmatine: Overview and Biological Significance In The Central Nervous Systemmentioning
confidence: 99%
“…In this condition, the sustained higher level of NO opens the N-methyl-d-aspartate (NMDA) channels through which the calcium influxes, causing neurotoxicity. After several hours of injury, the ADC/agmatine level increases and controls the iNOS and NMDA receptor functions [12,13]. In addition to ischemic or traumatic injury, agmatine has been found to have a positive effect on neurological diseases such as Alzheimer's disease, Parkinson's disease, epilepsy, and other mental diseases [14][15][16].…”
Section: Introductionmentioning
confidence: 99%